Penetapan Kadar Flavonoid Dan Uji Aktivitas Antibakteri Ekstrak Sereh (Cymbopogon nardus) Dan Temu Kunci (Boesnbergia pandurata Roxb) Terhadap Bakteri Streptococcus Mutans - Anita Kumala Hati; Niken Dyahariesti; Richa Yuswantina (Universitas Ngudi Waluyo, 2019)
Indonesia is rich in medicinal plants, including those that have the ability to inhibit bacterial growth, lemongrass (Cymbopogon nardus) and Fingerroots (Boesenbergia pandurata). Streptococcus mutans is a bacterium that causes dental caries. This Experiment want to determine the content of chemical compounds and the antibacterial activity of Lemongrass extract (Cymbopogon nardus) and Fingerroots (Boesenbergia pandurata) against Streptococcus mutans. The study was conducted experimentally with samples of lemongrass and Fingerroots. Extraction using maceration method using 70% Ethanol solvent. Phytochemical screening test with color test and determination of total flavonoid levels using a spectrophotometer. Antibacterial activity test uses the disk diffusion method against Streptococcus mutans. Phytochemical screening results of lemongrass extract and fingerroots with color test qualitative test showed positive containing flavonoids, saponins and tannins. In the test determination of total flavonoid levels, showed an average total flavonoid levels in lemongrass extracts of 48.61 mgQE / g and in Fingerroots extracts of 24.71 mgQE / g. The results of the antibacterial test against Streptococcus mutans obtained the largest average diameter of inhibitory zone in the extract of Fingerroots 5% w / v (11.167 mm), then the concentration of 5% w / v combination of lemongrass: Fingerroots 1: 2 (10.83 mm ), 2: 1 combination (10,067 mm). lemongrass (9.33 mm), 1: 1 combination (9,133 mm), Based on the Post Hoc test results that were comparable to positive controls were 5% fingerrots, combination of lemongrass: 1: 2 Fingerroots, and 2: 1 combination. The average total flavonoid level in lemongrass extract is more than the average total flavonoid content in Fingerroots. But in the same concentration 5% Fingerroots extract provides the greatest antibacterial inhibitory activities.